Analysis of Platelet Function from Thromboelastography Examination in Patients with Single and Multiple Antiplatelet Therapy after Percutaneous Coronary Intervention at Dr. Saiful Anwar Malang - Sasmojo Widito; Dadang Hendrawan; Dedy Irawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2020)
Each year, approximately 3 million people with coronary heart disease worldwide undergo percutaneous coronary intervention (PCI). Dual antiplatelet therapy (DAPT) with aspirin and P2Y12 inhibitors became the primary therapy for 6-12 months after PCI. DAPT can be continued > 12 months at a high risk of thrombosis. About 9-10% of patients with dual antiplatelet therapy still experience ischemia. The platelet function examination by thromboelastography (TEG). This research is an analytic observational study using a cross-sectional method. This study was conducted in Saiful Anwar General Hospital. Patients were divided into two groups: (1) on-single antiplatelet therapy; (2) on-dual antiplatelet therapy. The outcome measured result of the platelet function test was divided into standard, low platelet function, and platelet hypercoagulability. An analysis of the differences between single or multiple antiplatelet administration and the platelet function results was performed. There were 52 research subjects, each group of single and multiple antiplatelet therapies as many as 26 people, most of the subjects were male (82.6%) with a mean age of 57. The results of this study showed that there was no significant difference in the results of platelet function examinations between single and multiple antiplatelet therapies after 12 months of dual antiplatelet therapy